Nutritional value and sensory properties of common carp (Cyprinus carpio L.) fillets enriched with sustainable and natural feed ingredients. (June 2021) - Sobczak, M.; Panicz, R.; Eljasik, P.; Sadowski, J.; Tórz, A.; Żochowska-Kujawska, J.; Barbosa, V.; Dias, J.; Marques, A.
Abstract: Declines across global fishery stocks forced aquaculture feed manufacturers to search for new and sustainable components. Therefore, the aim of study was assessing nutritional value and sensory properties of meat of common carp ( Cyprinus carpio L.) fed for 116 days with two blends. The control feed contained 5% of fishmeal and vegetable oils (rapeseed and soybean) as sole fat sources. While in the experimental diet half of the fishmeal was replaced with a blend of microalgae ( Spirulina sp., Chlorella sp.), macroalgae ( Laminaria digitata ) and vegetable oil was replaced with salmon oil. Proximate composition, energy value, fatty acid profile of meat, nutritional characteristics of fat and protein as well as culinary properties of fillets were assessed. Fillets of carp fed experimental diet had a higher level of protein, lower level of fat and energy value. Intramuscular fat of fish fed with the experimental diet had a better parameters of quality. Protein in the meat of fish from both groups was characterized by a high quality comparing to the protein standard. Our study showed that meat of carp fed with experimental feed enriched with sustainable and natural feed ingredients can be a sensorily attractive source of nutritious ingredients in the human diet. Highlights: Feeds with salmon oil and algae meal improved chemical traits of C. carpio fillets. No differences in meat pH, texture, colour and cooking loss were registered variants. Fortified diets did not affect sensory properties of carp fillets. Fortified C. carpio constitute nutritionally attractive fish source for human diet.